Current trends and prospects for the development of sports nutrition worldwide and in Ukraine - Nemchenko, Alla; Mishchenko, Viktoriia; Vynnyk, Olena; Kurylenko, Yuliia; Teterich, Natalia (Current Issues in Pharmacy and Medical Sciences, 2026)
Sports nutrition (SN) represents a dynamically developing segment of the global food and dietary supplement market, driven by increasing interest in physical activity and healthy lifestyles. The study aimed to analyze current trends in the development of the sports nutrition market worldwide and in Ukraine, using the AthleteMarket retail network as a case study. The research was based on a review of specialized scientific literature, market reports, and an analysis of the product assortment offered by the AthleteMarket online store in 2021. Systemic, comparative, statistical, and graphical methods were applied. The global sports nutrition market demonstrates steady growth, with an average annual growth rate estimated at 8.1-11.0% and a projected value of up to USD 90 billion. The Ukrainian sports nutrition market is characterized by a high level of import dependence, with foreign manufacturers accounting for approximately 90.0% of available products. Analysis of the AthleteMarket assortment revealed the predominance of protein-based products and fat burners, with solid dosage forms (powders, capsules, tablets) representing 96.0% of the total range. Flavor variety remains an important factor for consumers, with vanilla, chocolate, and strawberry being the most common options. The AthleteMarket franchise model presents opportunities for business expansion within Ukraine. The sports nutrition market continues to expand globally and nationally, creating favorable conditions for further development. In Ukraine, market growth offers potential opportunities for domestic manufacturers and franchise-based retail expansion; however, further research and regulatory support are required to promote the rational use of sports nutrition products.